'The biological basis of cultural transmission' - Shea, N (Oxford University Press, 2006)
Once someone hits upon a good idea, others can learn it from them with ease, and develop it further. This oft-noted human ability is surely remarkable, but can it do explanatory work, and can it in turn be explained? Re-labelled ‘memetics’ this idea has generated excitement, but little insight. Sterelny’s great achievement is to transcend the platitude, to provide an illuminating account of the phenomenon. Ironically, to make his case he has to overcome the trait itself, at work in the transmission of the human sciences. For the great advances made by Chomsky and his followers are now part of the developmental environment of all students of human thought. Chomsky’s intellectual descendants have taken his approach to language as a paradigm, applying it to every facet of perception and cognition, proceeding via Fodor’s modularity of mind to the massive modularity hypothesis championed by evolutionary psychologists. When a regime is overextended, revolution is in order. Just as Chomsky overturned Skinner’s attempt to govern language with the (previously effective) apparatus of reward and punishment, Sterelny revolts against attempts to understand all human thought as analogous to the innate, modular language organ. Thought in a Hostile World is a detailed inventory of the tools needed to resist the dehumanising tyranny of modularity. And what exciting philosophy it is! Sterelny blends empirical detail with analytical rigour into an explosive mix, deploying his charges to recover two pieces of lost territory: folk biology and folk psychology. Neither, he argues, is like the language module, either in its operation or in its development; and he gives good evolutionary reasons why language should be an outlier, not an archetype.